Clinical implications of electrocardiographic bundle branch block in primary care. Issue 15 (25th May 2019) - Rasmussen, Peter Vibe; Skov, Morten Wagner; Ghouse, Jonas; Pietersen, Adrian; Hansen, Steen Møller; Torp-Pedersen, Christian; Køber, Lars; Haunsø, Stig; Olesen, Morten Salling; Svendsen, Jesper Hastrup; Melgaard, Jacob; Graff, Claus; et al.
Abstract : Objectives: Electrocardiographic bundle branch block (BBB) is common but the prognostic implications in primary care are unclear. We sought to investigate the relationship between electrocardiographic BBB subtypes and the risk of cardiovascular (CV) outcomes in a primary care population free of major CV disease. Methods: Retrospective cohort study of primary care patients referred for electrocardiogram (ECG) recording between 2001 and 2011. Cox regression models were used to estimate hazard ratios (HR) as well as absolute risks of CV outcomes based on various BBB subtypes. Results: We included 202 268 individuals with a median follow-up period of 7.8 years (Inter-quartile range [IQR] 4.9–10.6). Left bundle branch block (LBBB) was associated with heart failure (HF) in both men (HR 3.96, 95% CI 3.30 to 4.76) and women (HR 2.51, 95% CI 2.15 to 2.94) and with CV death in men (HR 1.80, 95% CI 1.38 to 2.35). Right bundle branch block (RBBB) was associated with pacemaker implantation in both men (HR 3.26, 95% CI 2.74 to 3.89) and women (HR 3.69, 95% CI 2.91 to 4.67), HF in both sexes and weakly associated with CV death in men. Regarding LBBB, we found an increasing hazard of HF with increasing QRS-interval duration (HR 1.25, 95% CI 1.11 to 1.42 per 10 ms increase in men and HR 1.23, 95% CI 1.08 to 1.40 per 10 ms increase in women). Absolute 10-year risk predictions across age-specific and sex-specific subgroups revealed clinically relevant differences between having various BBB subtypes. Conclusions: Opportunistic findings of BBB subtypes in primary care patients without major CV disease should be considered warnings of future HF and pacemaker implantation.